R&D Gaps in the Philippines - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1999)
Based on the chain of causality, R&D translates to innovation and to productivity/ technological progress, which ultimately leads to economic growth and prosperity. There exists a strong empirical support to positive relationship between effort levels in R&D and productivity. The objective of this paper is to determine and estimate the gaps in the Philippine R&D. Given the causality chain, the paper tries to identify the amount of corresponding/mandatory increase in research and development. It estimates the investment gaps using growth regression model involving total factor productivity of different countries on the one hand and the research and development expenditure and research and development manpower, on the other. On the basis of the frontier generated from the regression, Philippine R&D gap is computed. Results support the general conclusion of high rate of return to research and development. Results generated in this paper provide some policy insights regarding R&D in investments.
Keywords: 330; research and development sector; total factor productivity; investment gaps; increasing returns to scale